The combined effects of sleep and extreme heat exposure on cognitive function among older adults - Wensu Zhou; Xuezhu Li; Qiong Wang; Li Ling; Hui Zhang (Ecotoxicology and Environmental Safety)
Background: Extreme heat is linked to cognitive impairment. Normal sleep duration and good sleep quality can reduce cognitive impairment risks. However, the combined impact of sleep (duration and quality) and extreme heat on cognitive impairment is unclear. This study tests whether normal sleep duration and good sleep quality during a heatwave reduce cognitive impairment compared to poor sleep quality and long sleep duration in older adults. Methods: This study used cohort data from 9153 older adults. Extreme heat was defined as periods ≥ 3 days with daily minimum temperatures above the 92.5th percentile during the warm season. Cognitive function was assessed with the Mini-Mental State Examination (MMSE). Sleep duration was categorized as long, normal, or short, and sleep quality as good or poor. Six and four categories were used for combinations of heatwave exposure with sleep duration and quality, respectively. Cox regression models were applied for analysis. Results: Compared to those with long sleep duration during heatwaves, participants exposed to heatwaves with normal sleep duration had lower cognitive impairment risk (HR: 0.86, 95 %CI: 0.76–0.97). Those exposed to extreme heat with short sleep duration also showed lower cognitive risks (HR: 0.74, 95 %CI: 0.62–0.88). Compared to those with poor sleep quality during heatwave, participants with good sleep quality during heatwaves did not show significantly lower cognitive impairment risk (HR: 1.10, 95 %CI: 0.98–1.23). Conclusion: Older adults with normal or short sleep duration during heatwaves may face lower cognitive impairment risks, highlighting the importance of sleep guidance to protect cognitive health during extreme heat.